2014
DOI: 10.1257/mic.6.4.138
|View full text |Cite
|
Sign up to set email alerts
|

The Control Premium: A Preference for Payoff Autonomy

Abstract: We document individuals' willingness to pay to control their own payoff. Experiment participants choose whether to bet on themselves or on a partner answering a quiz question correctly. Given participants' beliefs, which we elicit separately, expected-money maximizers would bet on themselves in 56.4 percent of the decisions. However, participants actually bet on themselves in 64.9 percent of their opportunities, reflecting an aggregate control premium. The average participant is willing to sacrifice 8 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
57
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 43 publications
11
57
2
1
Order By: Relevance
“…Non-contractible intrinsic benefits of control are likely to bias principals towards keeping decision rights, possibly to the detriment of other parties within the organization and of organizational efficiency.4 For example, Fehr, Herz, and Wilkening (2013) found significant underdelegation of decision rights from principals to agents in experimentally controlled situations in which delegation would clearly be preferable for both parties in terms of expected monetary payoffs. Similarly, Owens, Grossman, and Fackler (2014) found that individuals are willing to sacrifice expected earnings to retain control.5 Falk and Kösfeld (2006) provided a related experimental finding by showing that limiting agents' choice sets can reduce positive reciprocity. However, none of these papers identifies the intrinsic value of decision rights.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Non-contractible intrinsic benefits of control are likely to bias principals towards keeping decision rights, possibly to the detriment of other parties within the organization and of organizational efficiency.4 For example, Fehr, Herz, and Wilkening (2013) found significant underdelegation of decision rights from principals to agents in experimentally controlled situations in which delegation would clearly be preferable for both parties in terms of expected monetary payoffs. Similarly, Owens, Grossman, and Fackler (2014) found that individuals are willing to sacrifice expected earnings to retain control.5 Falk and Kösfeld (2006) provided a related experimental finding by showing that limiting agents' choice sets can reduce positive reciprocity. However, none of these papers identifies the intrinsic value of decision rights.…”
Section: Introductionmentioning
confidence: 97%
“…4 For example, Fehr, Herz, and Wilkening (2013) found significant underdelegation of decision rights from principals to agents in experimentally controlled situations in which delegation would clearly be preferable for both parties in terms of expected monetary payoffs. Similarly, Owens, Grossman, and Fackler (2014) found that individuals are willing to sacrifice expected earnings to retain control. 5 Falk and Kosfeld (2006) provided a related experimental finding by showing that limiting agents' choice sets can reduce positive reciprocity.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…How decision authority is employed is then only secondary. Frey, Benz & Stutzer (2004) indeed argue that some people enjoy decision autonomy, and Benz & Frey (2008), Fuchs-Schündeln (2009), Bartling, Fehr & Herz (2013), and Owens, Grossman & Fackler (2014) provide empirical evidence for such preferences for decision autonomy. To isolate the importance of social preferences -no matter whether distributional or reciprocal concerns -for the allocation of authority, we conduct an experiment in which potential implementation problems never occur and are thus irrelevant if subjects are selfish in the sense that they maximize their own monetary payo↵s.…”
Section: Introductionmentioning
confidence: 98%